2018
DOI: 10.1038/s41434-018-0016-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PAK1 gene silencing on proliferation and apoptosis in hepatocellular carcinoma cell lines MHCC97-H and HepG2 and cells in xenograft tumor

Abstract: This study intends to explore the effect of the PAK1 gene silencing on apoptosis and proliferation of hepatocellular carcinoma (HCC) MHCC97-H and HepG2 cells and cells in xenograft tumor. MHCC97-H and HepG2 cells and mice with xenograft tumor in vivo were randomly divided into control, empty vector and PAK1 shRNA groups. Morphology and the expression of green fluorescent protein of MHCC97-H and HepG2 cells and cells in xenograft tumor were observed. MTT assay and flow cytometry were used to detect proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…In short, these results suggested that besides regulating PI3K/AKT and NF-κB pathway, knockdown of PAK1 could also regulate proliferation by inactivating MAPK pathway. Previous study demonstrated that PAK1 gene silencing might decrease proliferation and increase apoptosis of hepatocellular carcinoma cells by regulating the p53/p21 pathway [35]. In this study, we showed that knockdown of PAK1 increased the expressions of p53 and p21, and decreased the expressions of CyclinD1, MDM2 and CDK4.…”
Section: Discussionsupporting
confidence: 53%
“…In short, these results suggested that besides regulating PI3K/AKT and NF-κB pathway, knockdown of PAK1 could also regulate proliferation by inactivating MAPK pathway. Previous study demonstrated that PAK1 gene silencing might decrease proliferation and increase apoptosis of hepatocellular carcinoma cells by regulating the p53/p21 pathway [35]. In this study, we showed that knockdown of PAK1 increased the expressions of p53 and p21, and decreased the expressions of CyclinD1, MDM2 and CDK4.…”
Section: Discussionsupporting
confidence: 53%
“…33) From in vivo study, silencing of Pak1 gene decreases proliferation in xenograft tumor through the p53/p21 pathway. 34) In the present study, Pak1 was proved to be the target gene of miR-665. Interestingly, Pak1 promotes the proliferation and inhibits apoptosis via the Akt pathway.…”
Section: Discussionmentioning
confidence: 52%
“…Genistein downregulated the expression of AURKA and AURKB. PAK1 silencing has been shown to decrease cell proliferation [49]. High PAK1 expression in cervical cancer is associated with its pathological features including angiogenesis, upregulation of MMP2, metastasis and poor prognosis [50,51].…”
Section: Discussionmentioning
confidence: 99%